2003
DOI: 10.1097/00006982-200310000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Indocyanine Green Injected Into the Subretinal Space

Abstract: The results of this study suggest that the ICG of 1.25 mg/mL or higher concentration has toxicity to the outer retina of the rabbit and may cause adverse effects on the functional outcome after macular hole surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 27 publications
1
31
0
4
Order By: Relevance
“…In vitro and in vivo experimental studies demonstrated direct toxicity of ICG on the pigment epithelium and neurosensory re t i n a (11,(17)(18)(19). These adverse effects were correlated with the sodium concentration in the ICG solvent (20,21), osmolarity (10,22), ICG exposure time (17), and the concentration of the solution (8)(9)(10)(23)(24)(25)(26). Some of these investigators proposed the use of 5% glucose rather than balanced salt solution (BSS) to dilute ICG and pre f e r re d infracyanine green (noniodinated ICG) to ICG.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo experimental studies demonstrated direct toxicity of ICG on the pigment epithelium and neurosensory re t i n a (11,(17)(18)(19). These adverse effects were correlated with the sodium concentration in the ICG solvent (20,21), osmolarity (10,22), ICG exposure time (17), and the concentration of the solution (8)(9)(10)(23)(24)(25)(26). Some of these investigators proposed the use of 5% glucose rather than balanced salt solution (BSS) to dilute ICG and pre f e r re d infracyanine green (noniodinated ICG) to ICG.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23][24] However, there appears little doubt that in some circumstances ICG ILM peeling may be toxic to the retina with impaired acuity outcome, RPE pigmentary change and visual field defects being reported. [4][5][6][7][8][9][10]25 Factors that have been considered to be important in this toxicity include dye concentration, tonicity, contact time, and a photodynamic action associated with long wavelength endoillumination. We have used the dye at a concentration of 0.5 mg/ml (0.05%) diluted in 5 mg/ml in aqueous solvent and then one in 10 in BSS, with the shortest possible retinal contact time and use of a Bausch and Lomb Millenium or Alcon Accurus light source.…”
Section: Icg-assisted Ilm Peelingmentioning
confidence: 99%
“…2 This manoeuvre is greatly facilitated by the use of indocyanine green (ICG) dye; 3 there are, however, reports of adverse functional outcome when this dye has been used. [4][5][6][7][8][9][10] Nuclear sclerotic cataract is a very common complication of macular hole surgery, as a consequence of which some surgeons perform simultaneous 'prophylactic' clear lens extraction with lens implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Most notable among previous works on the photodegradation process in ICG is the work of Holzer et al 28 The study, however, is based on either very low ͑e.g., 10 M͒ or very high ͑e.g., 1.5 mM-toxic level 29 ͒ concentrations of ICG. Moreover, the work was predominantly geared toward characterizing the stability of above two concentrations of ICG ͑in different solvents͒ based on the initial probability of photobleaching.…”
Section: Introductionmentioning
confidence: 99%